2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31062
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Software Testing with Automated Feedback

Abstract: Computer science and software engineering courses commonly use automated grading systems to evaluate student programming assignments. These systems provide various types of feedback, such as whether student code passes instructor test cases. The literature contains little data on the association between feedback policies and student learning. This work analyzes the association between different types of feedback and student learning, specifically on the topic of software testing. Our study examines a second-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…These student perspectives reinforce the findings of Perretta, et al, that automated feedback improves student outcomes compared to manual feedback [2] and Eddy, et al, who found that introducing students to more complex topics such as Continuous Integration also increased their comfort with more basic tools such as Git [9].…”
Section: Thanks To Csg I Feel Like I Now Have An Edge Compared To My ...supporting
confidence: 83%
See 1 more Smart Citation
“…These student perspectives reinforce the findings of Perretta, et al, that automated feedback improves student outcomes compared to manual feedback [2] and Eddy, et al, who found that introducing students to more complex topics such as Continuous Integration also increased their comfort with more basic tools such as Git [9].…”
Section: Thanks To Csg I Feel Like I Now Have An Edge Compared To My ...supporting
confidence: 83%
“…Generally, students appreciate when their coursework is going to be relevant preparation for the industry, especially when those courses use industry tooling to do so [1]. More specifically, students appreciate tooling that provides automated feedback rather than having to wait on a mentor or professor [2]. Such tooling is even more beneficial to students when they are involved in the creation of the test harness itself as it prepares them for the industry where developers are often responsible for writing their own tests [3].…”
Section: Introduction and Relevant Literaturementioning
confidence: 99%
“…Souza et al shows that project-based learning in the context of software engineering education can be valuable [21], which is somewhat supported by our preliminary interview results. Perretta and DeOrio show that providing feedback on student-written testing (particularly the presence of false positives) can improve the quality of student tests [22], and we have several small exercises to do this in SoftDes. Effenberger and Pelánek describe a variety of code quality defects that are common in student code in introductory courses and suggest targeted feedback to help curb these practices [16].…”
Section: Related Workmentioning
confidence: 99%